An actin–ribonucleoprotein interaction is involved in transcription by RNA polymerase II - Percipalle, Piergiorgio (National Academy of Sciences, 2003)
To determine the function of actin in the cell nucleus, we sought to identify nuclear actin-binding proteins in the dipteran Chironomus tentans using DNase I-affinity chromatography. We identified the RNA-binding protein hrp65 as an actin-binding protein and showed that the C-terminal sequence of the hrp65-2 isoform is able to interact directly with actin in vitro. In vivo crosslinking and coimmunoprecipitation experiments indicated that hrp65 and actin are also associated in the living cell. Moreover, in vivo administration of a competing peptide corresponding to the C-terminal sequence of hrp65-2 disrupted the actin–hrp65-2 interaction and caused a specific and drastic reduction of transcription as judged by puff regression and diminished bromo-UTP incorporation. Our results indicate that an actin-based mechanism is implicated in the transcription of most if not all RNA polymerase II genes and suggest that an actin–hrp65-2 interaction is required to maintain the normal transcriptional activity of the cell. Furthermore, immunoelectron microscopy experiments and nuclear run-on assays suggest that the actin–hrp65-2 complex plays a role in transcription elongation.